MODAL SOSIAL ANTAR ETNIS PADA KOMUNITAS KAWASAN USAHA BATU BATA DI RW 027 KELURAHAN SAIL KECAMATAN TENAYAN RAYA KOTA PEKANBARU RIAU - Ferdinand Paska Pane; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted in the District Tenayan Raya Pekanbaru. The purpose of this study was to determine how to form inter-ethnic Social Capital Community contained in RW 027 and the factors that influence it. In the data collection researchers conducted observations and depth interviews. Subjects in this study amounted to 10 people. The data obtained was processed in the form of descriptive qualitative analysis. Sampling technique research using purposive sampling technique. The result from this research that social capital there are exist in the form: (1) trust, applied by the citizens by establish a relationship with good friends among them and maintaining trust with no cheating in their work and mutual trust in matters of employment in other words, not put an excessive suspicion. (2) Social Network, as seen in the sharing of information between citizens in finding or getting a job or workers, help each other in need and share in the joy, and mutual cooperation involving all citizens without distinction of each other in race, religion, race, and intergroup. (3) Social norms, formed themselves that nothing written in the rules in RW 027, but personally and awareness of citizens to know how to respect each other despite differences of culture, language and ethnicity and religion. And the factors forming social capital in society of RW 027 is : (1) has long shared with together routines making them an intense met each other, (2) Comfortable and safe sense, (3) Good communication and the openness of society to newcomers. In the social capital that exist in the society created by people trying not to disturb the public tranquility else and be friendly and humble among them and greeted each other so that at the end of the third factor makes people intimate and social capital solid.Keywords : Social Capital, Ethnic, Society